Coordination polymers of paramagnetic bis(leucinato)copper(ii) diastereomers: experimental and computational study of the stereoisomerism and conformations. Issue 34 (7th August 2020) - Vušak, Darko; Pejić, Jelena; Jurković, Mia; Szalontai, Gábor; Sabolović, Jasmina
Abstract : The syntheses, X-ray diffraction, solid state NMR and molecular modeling determined (dis)similarities between the coordination polymers of two bis(leucinato)copper(ii ) diastereomers. Abstract : This paper demonstrates the utility of joint applications of X-ray diffraction, solid state (ss) NMR, density functional theory (DFT) and molecular mechanics (MM) calculations for the determination of the stereochemistry of paramagnetic bis(aminoacidato)copper(ii ) compounds. Solution-based and mechanochemical syntheses of trans -bis(leucinato)copper(ii ) [Cu(Leu)2 ] with l - and dl -leucine using different solvents always resulted in the same two-dimensional coordination polymers of the ll (previously reported in the literature) and dl diastereomers. The X-ray crystal and molecular structure of trans -catena-[(μ-d -leucinato)(μ-l -leucinato)copper(ii )] (space group C 2) has symmetry unrelated d - and l -leucine side-chain conformations. An asymmetrical copper(ii ) dl -amino acid complex has not been observed so far in a non-centrosymmetric space group. Both ll and dl trans -[Cu(Leu)2 ] crystals have similar intermolecular bonding. The X-ray powder diffraction and magic-angle spinning (MAS) ssNMR information available from the polycrystalline bulk phase of the two compounds agree with their single-crystal results. Besides, the 2 H MAS ssNMR spectrum of the polycrystalline sample synthesized using dl -leucine showed weak signals which were ascribed to a small amount of the ll (dd ) stereoisomers. DFT calculations of the Fermi-contact contributions aided the 13 C and 2 H NMR spectral assignments. DFT conformational analyses of the ll and dl isomers revealed two Leu side-chain conformations as the energetically favorable ones in the gas phase and aqueous solution. These are exactly the conformations whose combinations occur in the observed crystal structures. Similar MM potential energies of ll and dl trans -[Cu(Leu)2 ] in the crystal lattices suggest that crystallization of dl over ll (dd) diastereomers should be attributed to kinetic rather than thermodynamic effects.